Effects of 8 weeks parent-accompanied swimming on physical capacity and intelligence in preschool children - Yichao Yu; Yichao Yu; Lei Xia; Lei Xia; Huiping Yan; Huiping Yan; Yifan Lu; Yifan Lu (Frontiers Media S.A., 2024)
This study aimed to explore the potential effects of 8-week parents-accompanied swimming on the physical capacity and intelligence of preschool children in China. Thirty-six boys (mean age 3.56 ± 0.27 years) were divided into three groups: the traditional physical exercise group (TP, n = 12), the accompanied swimming group (AS, n = 12) and the independent swimming group (IS, n = 12). Participants' physical capacity was assessed before and after the intervention using the following indicators: height, weight, distance of tennis ball throw, standing long jump distance, time for the 10-meter shuttle run, time for a two-legged continuous jump, sit-and-reach distance, and time on the walking balance beam. Intelligence was assessed at three points: pre-test, mid-test after 4 weeks, and post-test. Data were analyzed using a two-way repeated measures ANOVA, Bonferroni test (p < 0.05) and effect size. The time of the AS and IS groups to walk the balance beam was significantly lower than the TP group, with a difference of 1.81 s (p < 0.01, [95% CI −3.22 to −0.40], ES = 1.53) and 1.25 s (p < 0.05, [95% CI −2.66 to 0.16], ES = 0.81). At the mid-test, the IQ scores of the TP group were lower than the AS group (p < 0.05, [95% CI −12.45 to −0.96], ES = 0.89). Additionally, at post-test, the IQ scores of the TP group were significantly lower than those of both AS (p < 0.01, [95% CI −14.12 to −2.74], ES = 1.15) and IS groups (p < 0.01, [95% CI −12.53 to −3.31], ES = 1.21). Swimming enhances children's balance and IQ scores more than traditional physical exercises. Involving parents in swimming leads to a more significant increase in IQ scores within 4 weeks of initial swimming exercise.